2016
DOI: 10.1002/sres.2418
|View full text |Cite
|
Sign up to set email alerts
|

Modelling and Measuring Group Cohesiveness with Consonance: Intertwining the Sociometric Test with the Picture Apperception Value Test

Abstract: The purpose of this research is to model, measure and explain group cohesiveness through consonance. For this aim, we propose a holistic framework that combines the sociometric test with the novel Picture Apperception Value Test for defining group cohesiveness by assessing interpersonal attraction of group members through categorical values. The research approach is quantitative, classified both as inferential and quasi‐experimental. Findings indicate that the holistic framework serves as an effective model fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…Drawing on Van der Vegt and Janssen (2003) and Mudrack (1989), we define a cohesive work group as a group of individuals in a permanent or semi-permanent team who interact on a regular basis and feel their group to be highly competent at solving problems creatively. Instead of understanding work group cohesiveness on a macroorganizational level, we have shifted our focus to the micro-organizational level (Barile et al, 2016), such as the individual dynamics in innovative behaviour in the public sector. Mudrack (1989) found that although cohesiveness in a work group is highly beneficial, not all perspectives have been equally appreciated.…”
Section: Work Group Cohesivenessmentioning
confidence: 99%
See 2 more Smart Citations
“…Drawing on Van der Vegt and Janssen (2003) and Mudrack (1989), we define a cohesive work group as a group of individuals in a permanent or semi-permanent team who interact on a regular basis and feel their group to be highly competent at solving problems creatively. Instead of understanding work group cohesiveness on a macroorganizational level, we have shifted our focus to the micro-organizational level (Barile et al, 2016), such as the individual dynamics in innovative behaviour in the public sector. Mudrack (1989) found that although cohesiveness in a work group is highly beneficial, not all perspectives have been equally appreciated.…”
Section: Work Group Cohesivenessmentioning
confidence: 99%
“…For instance, a work group may consist of individuals with varying backgrounds, skills and experiences that benefit a group's overall performance and efficiency (Wang et al, 2006). Hogg (1993) observed that work groups can influence the attitudes and behaviours of their members, while Barile et al (2016) reported that group cohesiveness would have varying outcomes. For example, Tekleab et al (2009) found that the cohesiveness of a work group had negative outcomes, such as a lack of communication affecting the perceived safety of knowledge-sharing among members.…”
Section: Empowering In Public Sector In Norwaymentioning
confidence: 99%
See 1 more Smart Citation
“…According to Barile et al (2018) and Forsyth (2010), theorists decry the fact that cohesiveness is used to describe a vast array of group interactions and group functionality such that the concept itself lacks cohesion. This issue highlights the persistent deficiency within the body of knowledge concerning the discourse between the operational and conceptual definitions of cohesiveness (Casey-Campbell & Martens, 2009;Quince, 2001).…”
Section: Limits and Implications Of Social Cohesionmentioning
confidence: 99%
“…Mudrack (1989a) argues that despite decades of research on the topic of cohesiveness, the body of knowledge remains "dominated by confusion, inconsistency, and almost inexcusable sloppiness about defining the construct" (p. 45). Moreover, while the attraction between the individuals of the group is not a matter of mere fondness, the attraction between individuals to form a group together is the essence of social attraction which, when intensified, can permeate the entire group and transform the individuals from being conjoined to being cohesive (Barile et al, 2018;Forsyth, 2010;Mudrack, 1989a). The economic benefit of entrepreneurial collaboration is embedded in the strength and appeal of the social relationship between the entrepreneurs working jointly (David et al, 2020;Quince, 2001;Sulistyo & Ayuni, 2020).…”
Section: Limits and Implications Of Social Cohesionmentioning
confidence: 99%